Innovation and Leadership Style in Croatian Companies - Ivan Miloloža (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Split, Croatia, 6-8 September 2018, 2018)
Innovations present a key role of development and success of the companies. Fostering innovative approach in companies has several advantages. Innovation activities lead to competitive advantage, higher economic growth and better position on the global market. Furthermore, companies that are open to innovation, enable more efficient cooperation and communication between different business units through knowledge and information sharing. Motivated employees are ready to work on new and creative activities which lead to higher profitability and satisfied clients who prefer innovated products or services. Leadership style also effects on employees' results and their readiness to accept new ideas and changes that will improve business performances. The aim of this paper is to investigate the relationship between enterprise success and leadership styles. In order to determine characteristics of the relationship, multiple regression models have been conducted.
Keywords: O15; 330; leadership style; innovation; enterprises; multiple regression